If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(11 + -6x) + -3(7 + -4x) = 1 (11 * 2 + -6x * 2) + -3(7 + -4x) = 1 (22 + -12x) + -3(7 + -4x) = 1 22 + -12x + (7 * -3 + -4x * -3) = 1 22 + -12x + (-21 + 12x) = 1 Reorder the terms: 22 + -21 + -12x + 12x = 1 Combine like terms: 22 + -21 = 1 1 + -12x + 12x = 1 Combine like terms: -12x + 12x = 0 1 + 0 = 1 1 = 1 Add '-1' to each side of the equation. 1 + -1 = 1 + -1 Combine like terms: 1 + -1 = 0 0 = 1 + -1 Combine like terms: 1 + -1 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| x/3+6=3x-12+x/3 | | 15x+17x+2x=14+2 | | 5x+4(3x-10)=2(x-4) | | 16+9(12/3*2)-7 | | 4(7s-3)-8(s+2)= | | 2x+300=8x+120 | | 0.1(x+70)+1.3x=56 | | x2/3=9 | | 15x-13x=7-13 | | (8x+2)+(7-6x)=a | | 2/5(5k+35)-8 | | 6+5z-1=9z+15-2z | | 2x5/3+64=0 | | 8-6(x-3)=-2x | | -3(4x+12)= | | 20x-17x=20-14 | | x^3+7x^2=8 | | 62/3-216=0 | | x^3+7x^2-8= | | 40-6x=-(9x-4) | | 2x+4+x-1=180 | | 8c(4-c)=12 | | 21+(3x-19)=5+(5x-17) | | 8x^3+26x^2+15x=0 | | y=36-5x | | 3x-4*x+7=15 | | 4(b+3)=-8 | | 8x+(-5x+7)=-2 | | 2x^3+2x^2+3x+4=0 | | 8(x+3)=2(4x+3)+18 | | Y=-4(13)+967 | | 2(0)-4y=12 |